Effect of Non-thermal Atmospheric Pressure Plasma Activated Water Against Candida albicans Biofilms on Acrylic Surface - Singkharat, Pattarawan; Dechthummarong, Chanchai; Itthidecharon, Chintana; Wanachantararak, Phenphichar (Trends in Sciences, 2026)
Denture stomatitis, often caused by C. albicans biofilm formation on acrylic surfaces, presents a challenge in dental care. This study investigated the optimal conditions for generating non-thermal atmospheric pressure plasma-activated water (PAW) and its antifungal efficacy. Through a series of optimization experiments, the optimal parameters for yielding the highest concentrations of hydrogen peroxide and nitrate were found to be a 500 W of power input and a reduced distilled water volume of 500 mL. In subsequent analysis of PAW’s effect on planktonic C. albicans, a 12-minutes PAW demonstrated yielded the highest percentage of C. albicans inhibition, although it was not significantly different from the inhibition achieved at the 10-minutes PAW. Furthermore, immersing C. albicans biofilms on an acrylic surface for 10 min in 10 and 12-minutes PAW resulted in comparable mean C. albicans inhibition percentages of 82.0 ± 1.61% and 82.0 ± 3.50%, respectively. While the anti-biofilm efficacy of PAW was lower than that of 1% sodium hypochlorite (NaOCl), which was 98.6 ± 1.82% (p < 0.005). The 10 and 12-minutes PAW both markedly reduced biofilm viability across all immersion times with no significant differences observed between them at shorter durations (10, 30 min and 1 h). However, after 8 h of immersion, the 12-minutes PAW demonstrated a significant difference in biofilm inhibition from the 10-minutes PAW (p < 0.05). PAW is a chemically gentler alternative and indicates a promising, non-corrosive approach for future denture cleaning agents. Subsequent investigations should concentrate on augmenting PAWʼs anti-biofilm characteristics and examining its viability for clinical implementation in the prevention and management of denture stomatitis. HIGHLIGHTS Optimal non-thermal atmospheric pressure plasma (NTAPP) parameters (500 W, 500 mL of distilled water, 12 minutes activation time) maximized reactive oxygen and nitrogen species (RONS) generation and antifungal efficacy. Optimized plasma activated water (PAW) effectively inhibits establishedCandida albicans (C. albicans) biofilms on polymethyl methacrylate (PMMA) surfaces. PAW offers a gentler, non-corrosive antifungal alternative to sodium hypochlorite (NaOCl)for denture disinfection applications. GRAPHICAL ABSTRACT